Multifaceted Roles of Ferroptosis in Lung Diseases - Li, Yi; Yang, Ying; Yang, Yongfeng (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a distinct type of programmed cell death (PCD) that depends on iron and is characterized by the accumulation of intracellular iron, exhaustion of glutathione, deactivation of glutathione peroxidase, and promotion of lipid peroxidation. Recently, accumulated investigations have demonstrated that ferroptosis is strongly correlated with the initiation and development of many lung diseases. In this review, we summarized the contribution of ferroptosis to the pathologic process of lung diseases, namely, obstructive lung diseases (chronic obstructive pulmonary disease, asthma, and cystic fibrosis), interstitial lung diseases (pulmonary fibrosis of different causes), pulmonary diseases of vascular origin (ischemia-reperfusion injury and pulmonary hypertension), pulmonary infections (bacteria, viruses, and fungi), acute lung injury, acute respiratory distress syndrome, obstructive sleep apnea, pulmonary alveolar proteinosis, and lung cancer. We also discussed the therapeutic potential of targeting ferroptosis for these lung diseases.